P21. Neural correlates of cognitive control in motor processes. Issue 8 (August 2018) - Postigo-Alonso, B.; Hofmann, M.; Kühn, A.; Neumann, W.J.
Abstract : Introduction: The fronto-striato-subthalamic-pallidal network is involved in different aspects of motor and cognitive control (Jahanshahi et al., 2015 ), seeking as inhibition and conflict-induced slowing. Thus, in an automatic controlled mode of action. It has been proposed that this network 'communicates' in beta frequency oscillations ( ∼ 13–35 Hz) (Aron et al., 2016 ), which might reflect the cognitive control of motor processes. Objective: To characterize cognitive and motor demand on oscillatory beta activity in different cortical regions of this network for motor control and to explore its relationship with motor performance. Method: 20 right-handed healthy adults were assessed with a 64-channel EEG while performing a visual motor task. The data analysis included: time–frequency (TF) transformations using wavelets (width: 7); source extraction with LCMV beamformer from cortical areas of interest (Jha et al., 2015 ); permutation tests for statistical analysis of baseline corrected grand average of TF spectra aligned to the cue and movement onsets; and non-parametric correlation with Spearman's Rho between TF spectra and behavioral measures All p-values were FDR corrected. Results: Participants significantly increased reaction time, movement time and trajectory error during the controlled versus the automatic condition. A significant decrease in beta was found in all sources of interest (M1R, M1L, pre-SMA & SMA) aligned with the onset of the cue and movement initiation, which prolonged during movement. Only in the SMA, beta decreases significantly higher in the automatic than in the controlled condition aligned to the cue onset. A negative correlation between high beta reactivity and trajectory error before and during movement onset indicated that more power in high-beta oscillations was associated with less trajectory error. Moreover, a greater difference in high power between two conditions is associated with increased trajectory error. Conclusions: Less decrease in beta oscillations in the SMA during controlled -compared to the automatic condition would reflect its implication in the cognitive control of motor processes. It might enable future therapeutic intervention for neurological patients.